Risk of cancer in patients with scleroderma: a population based cohort study. Issue 8 (1st August 2003) - Hill, C L; Nguyen, A-M; Roder, D; Roberts-Thomson, P
Abstract : Background: Previous studies have suggested an increased risk of cancer among patients with scleroderma. Objective: To study a population based cohort of patients with scleroderma in South Australia. Methods: Subjects with scleroderma were identified from the South Australian Scleroderma Registry established in 1993. All subjects on the scleroderma registry were linked to the South Australian Cancer Registry to identify all cases of cancer until 31 December 2000. Standardised incidence ratios (SIRs) for cancer for subjects with scleroderma were determined using the age- and sex-specific rates for South Australia. Results: In 441 patients with scleroderma, 90 cases of cancer were identified, 47 of which developed after inclusion on the scleroderma registry. The SIRs for all cancers among these patients were significantly increased (SIR=1.99; 95% confidence interval (95% CI) 1.46 to 2.65) compared with the cancer incidence rates for South Australia. The SIRs for lung cancer (SIR=5.9; 95% CI 3.05 to 10.31) were also significantly increased. The SIRs for all cancers among the subgroups with diffuse scleroderma (SIR=2.73; 95% CI 1.31 to 5.02) and limited scleroderma (SIR=1.85; 95% CI 1.23 to 2.68) were significantly increased. Conclusions: This population based cohort study provides evidence that scleroderma is associated with cancer, and in particular, lung cancer. In addition, both diffuse and limited forms of scleroderma are associated with a similarly increased risk of cancer.